Sport types and time spent playing sport are associated with eating pattern among young Brazilian athletes - Noll, M.; Rodrigues, A. P.; Silveira, E. A. (Asian Journal of Sports Medicine, 2019)
Background: Nutritional studies on athletes have focused on the intake of nutrients and nutritional supplements. The lack of sufficient evidence on eating pattern is challenging for those advising athletes on their daily dietary patterns during training and competitions.